Accounting for Mathematics Performance of High School Students in Mexico: Estimating a Coordination Game in the Classroom - Todd, Petra; Wolpin, Kenneth I. (Journal of Political Economy, 2018)
This paper estimates a model of the effort decisions of students and teachers in a classroom setting to understand the performance of Mexican high school students on curriculum-based examinations. The model allows for student heterogeneity in initial mathematics preparation and knowledge preference and for teacher heterogeneity in instructional ability and preferences for student knowledge. Survey data include multiple measurements of student and teacher effort, student and teacher preferences, student initial knowledge, and teacher ability. The most important factor accounting for poor performance, the lack of sufficient prior preparation, suggests a mismatch between the curriculum content and entering grade-level mathematics knowledge.